Reflections on pharmaceutical performance in an outpatient clinic of transgender users: Facilitators and Challenges (Research, Society and Development, 2022)
This study presents a report of pharmacists and pharmacy undergraduates who work in a Trans outpatient clinic in view of their experiences and experiences, presenting the barriers faced and the strengths in the context of outpatient interprofessional work. This is an experience report on the pharmaceutical care service developed at the Trans User Reception Outpatient Clinic of the Federal University of Sergipe, located in the municipality of Lagarto/SE. In this scenario, the role of the pharmacist in the multidisciplinary team stands out, since his presence in the outpatient clinic can provide improvements by identifying the needs of the user and referring him to specialized professionals and, not necessarily, resorting solely to pharmacological therapies. Given the challenges faced, it is verified that there should be a reorientation in the training process, and the experience and performance of the pharmacist add in care and complementary way with regard to comprehensive health care of the trans population. Thus, one can minimize weaknesses, conquer space in a multidisciplinary team and have recognition of their functions.